Factors Associated with Severity of COVID-19 Illness in Cancer Patients - Nasir, Maimoona; Nadeem, Muhammad; Amjad; Umair; Mehmood, Faisal (Pakistan Armed Forces Medical Journal, 2023)
Objective: To identify the various risk factors associated with severe COVID-19 complications in cancer patients. Study design: Cross-sectional study. Place and duration of study: Combined Military Hospital, Rawalpindi Pakistan, from Jun to Nov 2022. Methodology: Seventy-one cancer patients with COVID-19 infection confirmed by PCR test on nasopharyngeal swab were included in the study. They were assessed for their, ECOG status, smoking habit, comorbidity, vaccination status, cancer type, lung involvement and chemotherapy after written informed consent. COVID-19 symptoms were categorized. Results: Out of 71 patients included in the study, 16(22.5%) cancer patients had asymptomatic COVID-19 infection, 34(47.9 %) patients had mild symptoms, 13(18.3%) had moderate disease, and 7(9.9%) had severe COVID-19 illness. A significant association was found between severity of COVID-19 illness with age, gender, ECOG status, presence or absence of comorbid, vaccination status and type of malignancy (p-value<0.05). Conclusions: Old, male, frail and unvaccinated patients with comorbidity more frequently developed serious COVID-19 disease. Patients with hematologic or lung malignancies had worse outcomes, while vaccinated ones were protected against severe disease. Chemotherapy or smoking had no significant impact on the severity of COVID-19 illness.